Should we still monitor QTc duration in frail older patients on low-dose haloperidol? A prospective observational cohort study. (2nd July 2020) - Castro, Ellen; Körver, Frank; Merry, Audrey; van Moorsel, Fieke; Hazebroek, Mark; Smid, Machiel; Ploux, Sylvain; Bordachar, Pierre; Prinzen, Frits; Sipers, Walther; Strik, Marc
Abstract: Background: Haloperidol at high dosage is associated with QTc prolongation and polymorphic ventricular arrhythmia but the effects of low-dose haloperidol remain unknown. Objective: To evaluate the effects of low-dose haloperidol on QTc-duration in frail hospitalized elderly patients with delirium. Methods: A prospective observational study including hospitalized patients aged ≥70 years with Groningen Frailty Index-score > 3. We included 150 patients who received haloperidol and 150 age- and frailty-matched control patients. Serial ECG recordings were performed at hospital admission and during hospitalization. QT-interval was corrected according to Framingham (QTc). Patients were grouped according to baseline QTc in normal (nQTc), borderline (bQTc) or abnormal (aQTc). Primary outcome was change in QTc-duration between first and second ECG. Potentially dangerous QTc was defined as QTc >500 ms or an increase of >50 ms. Results: Patients in the haloperidol group (48% male, mean age 85y, nQT n = 98, bQT n = 31, aQT n = 20) received an average dose of 1.5 mg haloperidol per 24 hours. QTc decreased in patients with borderline (mean − 15 ± 29 ms, P  < 0.05) or abnormal (−19 ± 27 ms, P  < 0.05) QTc at baseline, no patients developed dangerous QTc-duration. In the control group (41% male, mean age 84y, nQT n = 99 bQT n = 29, aQT n = 22) QTc decreased to a similar extent (bQT −7 ± 16 ms, aQTc −23 ± 20 ms). Conclusion: A trend to QTc shortening was seen, especially in patients with borderline or abnormal QTc at baseline, regardless of haloperidol use. These findings suggest that ECG monitoring of frail elderly patients who receive low-dose haloperidol, may not be necessary.